Characterization of chrysanthemum (Chrysanthemum grandiflorum ) varieties using ISSR markers - KUMAR, GUNJEET; SINGH, KANWAR PAL; PRASAD, K V; VERMA, NIDHI; NAMITA, NAMITA; PANWAR, SAPNA (The Indian Journal of Agricultural Sciences, 2015)
Identification and characterization of new varieties is essential to meet DUS testing, address IPR issues and their utilization and conservation. A total of 68 ISSR primers were screened and out of these 23 primers which gave sufficient amplification were selected for the study. These primers produced 169 bands, out of which, 149 were polymorphic with a polymorphic percentage of 88.17%. The ISSR primers namely ISSR 22, ISSR 26, ISSR 38 generated least number of bands, i.e. four of which only two were polymorphic with a polymorphism of 50% in ISSR 22. The polymorphism across all the ISSR markers ranged between 66.7% (ISSR37) to 100% (ISSR 21, ISSR 25, ISSR 26, ISSR 28, ISSR 30 and ISSR 811). The resolving power of band (Rp) produced by ISSR markers ranged from 0.66 to 7.64 for primer ISSR 38 and ISSR 31 with a mean value of 86.48 for all the primers. The correlations between Rp and number of varieties identified by each ISSR primer (0.92) were fairly high. The value of polymorphic information content (PIC) was ranged from 0.023 (ISSR 809) to 0.553 (ISSR 26) with a mean value of 0.35 over all the primers. The UPGMA dendrogram based on ISSR analysis indicated that the outlier species were 74% dissimilar with other varieties and grouped separately. The cultivars Maghi Orange and Maghi Yellow had around 90% similarity and were close to cultivar Maghi White at over 80% similarity level. ISSR markers were proved to be useful for the characterization of the genotypes for their efficient utilization, management and IPR protection.